Características clínicas e epidemiológicas da doença de Haff - Silva, Roberto César de Moura (2024)
Haff disease, first identified in Europe in the early 20th century, is a rare condition characterized by sudden rhabdomyolysis without obvious traumatic causes, associated with the consumption of certain fish and shellfish. Symptoms include intense muscle pain, weakness, and dark urine, which can lead to serious complications such as acute kidney injury (AKI) due to the release of myoglobin. Although initially reported in Haff Bay, Germany, the disease has emerged globally, with a notable incidence in the Brazilian Amazon, where fish consumption is culturally significant. This pattern underscores the urgency for detailed studies in this specific context to understand the disease's etiology and develop preventive and therapeutic measures. Investigating Haff disease requires a multidisciplinary approach, encompassing toxicology, epidemiology, clinical medicine, and public health, aiming to enhance health surveillance and preparedness for future outbreaks. This study aims to investigate the clinical and epidemiological characteristics of Haff disease worldwide through a systematic and bibliometric review of cases described in the literature. The methodology employed included the use of the software StArt and VOSviewer for data analysis, enabling a rigorous evaluation of relevant studies. Renowned scientific databases were accessed, following strict inclusion and exclusion criteria, to identify patterns and associated factors. The analysis incorporated sociodemographic, epidemiological, clinical, and laboratory variables, providing a comprehensive understanding of Haff disease. This work aims to capture the interest of other researchers by revealing the complexities and potential research avenues to understand this underexplored condition. Key words: Haff disease; Rhabdomyolysis; Acute kidney injury; Epidemiology.